ESKATOLOGI: HARI PEMBALASAN PERSPEKTIF TAFSIR AL-AZHAR - Roffi, Riza Wahyu; Mubarok, Muhammad Ngali (El-Rusyd, 2024)
Eschatology is the study of life after death in the afterlife. Eschatology is an interesting study in philosophy and religion because it discusses belief in things that discuss metaphysics or events beyond human reason. This study itself will remain a very interesting study to discuss in this millennial era. In the discussion of eschatology, this is mentioned in Islam which is explained in the Quran. According to Buya Hamka in Tafseer Al-Azhar, eschatology itself is the final event of every living being. Thus eschatology is closely related to Ad-din. It is interpreted as two places that will be inhabited by God's creatures according to the value of their devotion while in the world, namely Heaven and Hell. In this research, the research method used is Qualitative method with content analysis research type. This study found that eschatology is an important part of Islamic teachings that remind humans of the true purpose of life. A deep understanding of Yaumid Din encourages individuals to improve their morals, multiply good deeds, and get closer to Allah. Belief in the day of reckoning plays a role in shaping moral awareness and obedience in this world as a preparation for the afterlife.